2021
DOI: 10.1002/mar.21495
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of consumers' intention to use biometric facial recognition as a payment method

Abstract: Interests in technology innovation has increased in many organizations. Collaborations among technology providers and marketers are occurring as they integrate these biometric technologies as a means of convenience and security for their consumers. Despite the benefits of integrating new technology to ease consumers' shopping experience, consumers are skeptical about using technology that requires their biometric data. Two studies were conducted to investigate the trust toward these biometric payment systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 115 publications
2
37
0
Order By: Relevance
“…Zhang and Kang (2019) found that such an intention is influenced by several factors including security, visibility, expected effort and perceived usefulness (PU). In a study explaining consumer intention to use biometric facial recognition for payment, Moriuchi (2021) confirmed a trust–attitude–intention hierarchy. Moreover, Zhong et al.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Zhang and Kang (2019) found that such an intention is influenced by several factors including security, visibility, expected effort and perceived usefulness (PU). In a study explaining consumer intention to use biometric facial recognition for payment, Moriuchi (2021) confirmed a trust–attitude–intention hierarchy. Moreover, Zhong et al.…”
Section: Introductionmentioning
confidence: 76%
“…Zhang and Kang (2019) found that such an intention is influenced by several factors including security, visibility, expected effort and perceived usefulness (PU). In a study explaining consumer intention to use biometric facial recognition for payment, Moriuchi (2021) confirmed a trust-attitudeintention hierarchy. Moreover, Zhong et al (2021), using an extended Technology Acceptance Model (TAM), found that perceived enjoyment, perceived ease of use (PEU) and PU positively affect attitude towards FRP, which in turn lead to usage intention.…”
mentioning
confidence: 78%
“…These transactions are quick and touchless, and the “currency” cannot be lost nor is it stored on a device that can be misplaced or powered down. Research suggests that consumers perceive facial recognition as a more secure form of payment for in-store (vs. online) transactions (Moriuchi, 2021 ). Still, consumers remain concerned about their privacy and security.…”
Section: Dps 20 Facilitatorsmentioning
confidence: 99%
“…Several firms have begun to accept DPS 2.0 as the new normal. However, a keyword search for DPS 2.0 (digital payment systems) and cashless economies among the top 50 marketing journals listed within SJR (i.e., Journal of Marketing , Journal of Consumer Research , Journal of Marketing Research , and Marketing Letters ) yielded three marketing papers on the topic in the last 10 years (i.e., Cwynar et al, 2021 ; Moriuchi, 2021 ; Park et al, 2021 ). As such, an understanding of how DPS 2.0 will impact consumers’ movement into a cashless economy is an important dialog to pursue.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that convenience, privacy and financial risk have a significant influence on perceived value and trust which play an important role on consumers' decision-making. In addition, Moriuchi (2021) considered usability of the technology and consumers' psychology by using unified theory of acceptance and use of technology (UTAUT) and theory of mind (ToM) theory to understand potential barriers and opportunities consumers face when using FRP.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%